A tessitura do imaginário na obra juvenil Kafka e a Boneca viajante de Jordi Sierra i Fabra: uma perspectiva teórica de Wolfgang Iser - Vale, Márcia Miranda Chagas (2019)
This master thesis aims to understand actuation of the imaginary and its development for the composition and production of plot of youthful work Kafka e a boneca viajante, by Sierra i Fabra, as well as there is intention of dialoguing and analyzing fictional discourse of this work as product of the human self-representation staging, taking it as a narrative that lists the worlds transgression by having as a starting point the construction of imaginary letters written by the character Franz Kafka, to girl Elsi, in order to make her overcome the loss pain of her doll Brígida, an imaginary journey is staged in which unpredictability of events enables a metafictional and defragmented tessitura. In view of narrative nuances, this research aims to problematize the work creating act on the assumption that Sierra i Fabra was inspired by the supposed experience of the writer Franz Kafka, in the year 1923, in Berlin, Germany, when he creating letters for a girl who had lost her doll but these letters were never found. In this way, the research concerns its interest in discussing the imaginary as a plot building basic element, for this purpose, this discussion is based on the theoretical conception of Wolfgang Iser (2013) who says that the fiction texts are integrated to the given world, from the triple: real, fictitious and imaginary; understanding that these elements align with the text as perspectives of a literary anthropology. By focusing on the desired objectives, this research is articulated with a qualitative and exploratory approach that starts from a bibliographical survey: theoretical and critical, based on the book O fictício e o imaginário: Perspectivas de uma Antropologia Literária (ISER, 2013), besides the supports: O ato da leitura (1996; 1999a) and the collection of VII colóquio da UERJ: Teoria da ficção: Indagações à Obra de Wolfgang Iser (ROCHA, 1999); furthermore, there are references of Lima (2006, 2007; 2009), Coleredige (2018), Sartre (1996; 2017), Castoriadis (2000), Eco (2002; 2017), Cassier (2011), Bateson (2000), among others who contribute to the corpus of this research. In this regard, Kafka e a boneca viajante will be presented as a work that opens for the enactment of a figurative world, in which pretending enables conduct of the imaginary game, unforeseen, unusual and that brings perspectives of truths which are not reached, except through the course of a literary fiction text established through imaginary tessitura